A sock is a pocket for your toes : a pocket book - Scanlon, Liz Garton; Preiss-Glasser, Robin (New York : HarperCollins, 2004)
A poetic celebration of non-traditional pockets and what they hold, pointing out that a sock is a pocket for your toes and a vase is a pocket for a rose.
Presch-2.
A Junior Library Guild selection.
Keywords: Pockets -- Juvenile poetry; Children's poetry, American; Pockets -- Poetry; American poetry